Internet auctions in marketing: The consumer perspective - Antje Möllenberg (Technische Universität Braunschweig, Institut für Marketing, 2003)
Internet auctions for consumer are among the most popular and most successful business models in electronic commerce. Research so far, however, has focused on prerequisites and consequences of auctions as a marketing intstrument of suppliers. Even though it is a key success factor from a marketing perspective, the demand side has not inspired similar attention. This paper focuses on the attitudes, motives, and behavior of auction customers. It shows why ccurrent beliefs about bidder characteristics are myths. Taking these misconceptions as a starting point, the existence of an experiential and a pragmatic type of auction customer is proposed. An explorative empirical study looking for the characteristics of both types of auction customers is described. Results indicate that less than half of auction shoppers in the sudy are experiential oriented. Except substantial additional demand concerning technological and emotional qualities of auctions these shoppers do not differ dramatically from pragmatic oriented shoppers. Both types are open-minded towards further development of consumer auctions to commercial marketplaces. Business models of auctioneers and suppliers should concentrate on the basic utility of the auction algorithm by facilitating individual matchmaking instead of pursuing costly additional utility by promoting the entertainment value of auctions.
Keywords: 650; Auktion; E-Business; Geschäftsmodell; Konsumentenverhalten